2005
DOI: 10.1111/j.1365-3040.2005.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate promotes emission of mercury vapour from plants

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Reduction of Hg(II) to Hg(0) in the leaves with transpiration of Hg(0) as a consequence was also observed . Ionic Hg(II) is carried by the transpiration flow from roots to leaves and then reduced to Hg(0) in the apoplastic spaces of the spongy mesophyll by ascorbic acid . Although the putative reduction with ascorbic acid has been described in barley, authors suggested that reduction of Hg(II) to Hg(0) occurs in macrophytes .…”
Section: Effects Of Shootsmentioning
confidence: 97%
See 1 more Smart Citation
“…Reduction of Hg(II) to Hg(0) in the leaves with transpiration of Hg(0) as a consequence was also observed . Ionic Hg(II) is carried by the transpiration flow from roots to leaves and then reduced to Hg(0) in the apoplastic spaces of the spongy mesophyll by ascorbic acid . Although the putative reduction with ascorbic acid has been described in barley, authors suggested that reduction of Hg(II) to Hg(0) occurs in macrophytes .…”
Section: Effects Of Shootsmentioning
confidence: 97%
“…On the contrary, in I. aquatica , an exposure to HgCl 2 ‐spiked nutrient medium for a period of 4 d, followed by 4 d without any addition of external Hg, resulted in a 3‐fold increase of MeHg concentrations in the shoots as compared with levels directly after the Hg exposure, suggesting methylation of Hg in planta . Reduction of Hg(II) to Hg(0) in the leaves with transpiration of Hg(0) as a consequence was also observed . Ionic Hg(II) is carried by the transpiration flow from roots to leaves and then reduced to Hg(0) in the apoplastic spaces of the spongy mesophyll by ascorbic acid .…”
Section: Effects Of Shootsmentioning
confidence: 98%
“…Laboratory evidence has shown that plants (53)(54)(55), fungi (23,56,57), bacteria (58), and algae (59) can transform other more easily reducible metals, including Au, Ag, Se (as H2SeO3), Hg, and Te, to their elemental states both intraand extracellularly. When mechanisms have been proposed, they typically have involved enzymes; however, ascorbic acid was implicated when Hg 2+ was transformed to Hg 0 (g) in barley leaves (60). Theoretically all of these metal cations could be transformed by a reducing agent weaker than ascorbic acid (Table S1 in Supporting Information).…”
Section: Mechanism Of Cumentioning
confidence: 99%
“…st is an empirical input value and suggested as 5-25 ng m −3 depending on the specific land use. Battke et al (2005Battke et al ( , 2008 and Heaton et al (2005) reported that plants have the ability to reduce the Hg II to Hg 0 in foliar cells through reducing ligands (e.g., NADPH). To propose a more physically robust modeling scheme, the redox processes in foliage and the role of ligands on Hg uptake need to be better understood.…”
Section: Modeling Of Air-surface Hg 0 Exchange Fluxmentioning
confidence: 99%